The meaning of Laurier’s Advertising Message version #ThisistheGirlsway comfortable be yourself! on Youtube : (Charles Shanders Pierce Semiotic Analysis) - nuzhatussholehah, Nuzhatussholehah; Jamiati, Jamiati KN (Universitas Ahmad Dahlan, 2022)
Laurier's ad version of #ThisIsTheGirlsWay Comfortable Being Yourself takes a problem that often occurs in today's environment, and of course it is related to the Brand. This non-commercial advertisement is